Power reserve control strategy in the left‐side of maximum power point for primary frequency regulation of grid‐connected photovoltaic systems. Issue 2 (10th December 2021) - Yan, Xiangwu; Wang, Chenguang; Rasool, Aazim; Liang, Baixue; Ma, Hongbin
Abstract: The traditional method of operating photovoltaic (PV) systems on the right side of the maximum power point (MPP) may cause the voltage to be close to the open‐circuit voltage of the PV panel, resulting in a large oscillation of the PV power. In contrast, the change in d P /d U value of the curve on the left of the MPP is small, which is more conducive to adjusting the output power of the PV. A frequency regulation control strategy is proposed for a single‐stage PV power plant (PVPP), maintaining the PV string operating on the left side of the MPP. This paper proposes an optimal step‐size calculation method based on the flexible power tracking evaluation function. This calculation method is suitable for PV operating on the left side of the MPP and can improve the dynamic and steady‐state performance of the PV power tracking process. In addition, the system response is analyzed by establishing a small‐signal model with PV operating on the left side of the MPP. Finally, simulations and experiments verify the correctness and accuracy of the proposed primary frequency regulation strategy and step‐size calculation method.